Significant polar vasculosis in a patient with a 30-year history of type 2 diabetes. (12th November 2019) - Oda, Yasuhiro; Yamanouchi, Masayuki; Mizuno, Hiroki; Hiramatsu, Rikako; Suwabe, Tatsuya; Hoshino, Junichi; Sawa, Naoki; Ohashi, Kenichi; Fujii, Takeshi; Ubara, Yoshifumi
Abstract : Summary: We report the renal histology of a 66-year-old man with hypertension, cardiovascular disease, and a 30-year history of type 2 diabetes mellitus with proliferative diabetic retinopathy, diabetic neuropathy, and diabetic foot status post toe amputation. Urinary protein excretion was 1.4 g/gCr, serum creatinine level 0.86 mg/dL, estimated glomerular filtration rate 69 mL/min/1.73 m 2, and HbA1c 13–15%, despite using insulin. Light microscopy showed global glomerulosclerosis in 37% of the glomeruli, but the remaining glomeruli were intact. Significant polar vasculosis was present, while arteriolar sclerosis was mild. Electron microscopy revealed a thickened glomerular basement membrane, which is compatible with the early stage of diabetic glomerulopathy. The presented case was unique because glomerular changes seen typically in diabetes were not seen in the patient, despite the long-standing history of diabetes and diabetic comorbidities, while prominent polar vasculosis was found. Polar vascular formation helps preserve the glomeruli by allowing hyperosmotic blood bypass the glomeruli; this decreases intraglomerular pressure and minimizes glomerular endothelial damage. Learning points: A 66-year-old man with a 30-year history of type 2 diabetes mellitus with poor glycemic control underwent renal biopsy, which showed scarce glomerular changes typically seen in diabetic kidney disease and instead revealed significant polar vasculosis. Past studies demonstrated that the increased small vessels around the vascular hilus in diabetic patients originated from the afferent arterioles and drained into the peritubular capillaries. Polar vascular formation may preserve glomerular function by allowing the blood flow to bypass the glomeruli and decreasing the intraglomerular pressure, which minimizes endothelial damage of the glomerular tufts.